2010
DOI: 10.4049/jimmunol.1001213
|View full text |Cite
|
Sign up to set email alerts
|

BLT2 Is Upregulated in Allergen-Stimulated Mast Cells and Mediates the Synthesis of Th2 Cytokines

Abstract: Mast cells are effector cells that mediate the allergic response through Ag stimulation of IgE bound to FcεRI. In allergic reactions, cross-linking of the surface receptors for IgE on mast cells results in the synthesis of Th2 cytokines such as IL-4 and IL-13, which are critical for the initiation and progression of the allergic response. Despite the important roles of these cytokines, the signaling mechanism by which Ag stimulation mediates the production of IL-4 and IL-13 in mast cells is not clearly underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 45 publications
3
64
0
Order By: Relevance
“…The BLT2-mediated NOX1 upregulation-dependent pathway has also been shown to promote the secretion of IL-8 from human mast cells in response to the pro-inflammatory cytokine IL1beta, contributing to angiogenesis (Kim et al, 2010d). Another study indicated that BLT2-stimulated NOX1 upregulation is a downstream signaling route that mediates the synthesis of Th2 cytokines (IL-4 and IL-13) in antigen-stimulated bone marrowderived mast cells (Cho et al, 2010). The mechanism through which BLT2 mediates NOX upregulation has not yet been clearly demonstrated.…”
Section: Blt1/blt2 and Noxmentioning
confidence: 99%
“…The BLT2-mediated NOX1 upregulation-dependent pathway has also been shown to promote the secretion of IL-8 from human mast cells in response to the pro-inflammatory cytokine IL1beta, contributing to angiogenesis (Kim et al, 2010d). Another study indicated that BLT2-stimulated NOX1 upregulation is a downstream signaling route that mediates the synthesis of Th2 cytokines (IL-4 and IL-13) in antigen-stimulated bone marrowderived mast cells (Cho et al, 2010). The mechanism through which BLT2 mediates NOX upregulation has not yet been clearly demonstrated.…”
Section: Blt1/blt2 and Noxmentioning
confidence: 99%
“…A subsequent study also described BLT 2 R mRNA in BMMC after 4 weeks of culture and indicated that either the BLT 1 R antagonist U75302 or the BLT 2 receptor antagonist LY255283 inhibited LTB 4 -induced BMMC chemotaxis, although no additive effect was observed after combination of the two receptor antagonists (Lundeen et al, 2006). In addition, antigen stimulation increased BLT 2 R expression in murine BMMCs (Cho et al, 2010a). In support of a functional murine MC BLT 2 receptor, the BLT 2 receptor agonists 12-HHT and 12(S)-HETE have also been reported to induce BMMC migration (Lundeen et al, 2006;Okuno et al, 2008).…”
Section: Mast Cells Experiments In Human Umbilical Cord Blood-derivementioning
confidence: 99%
“…The amplification protocol for both the first round and nested PCR included 27 cycles of denaturation 95°C for 30 s, annealing at 61°C for 40 s, and elongation at 72°C for 45 s. For Nox1, the size of amplification product is 305 bp. The primers for mouse BLT1 were 5Ј-GCATGTCCCTGT-CTCGTT-3Ј (forward) and 5Ј-CGGGCAAAGGCCTTAGT-ACG-3Ј (reverse), and the primers for mouse BLT2 were 5Ј-CAGCATGTACGCCAGCGTGC-3Ј (forward) and 5Ј-CGAT-GGCGCTCACCAGACG-3Ј (reverse) (25). The PCR protocol for mouse BLT1/2 entailed 35 cycles of denaturation at 94°C for 30 s, annealing at 68°C for 30 s, and elongation at 72°C for 30 s followed by extension at 72°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%